The Influence of Knowledge and Work Motivation on Human Resource Development with Job Satisfaction as a Moderating Variable at the UPTD Child Social Service Center of Padang Sidempuan–Panyabungan - Abdi Negara Hasibuan (Utan Kayu Publishing, 2026)
This study aims to analyze the effect of knowledge and work motivation on human resource development with job satisfaction as a moderating variable at the UPTD Child Social Service Center of Padang Sidempuan–Panyabungan. The research is motivated by the importance of improving the quality of human resources in social services, which requires competence, work enthusiasm, and individual job satisfaction. A quantitative approach was applied using a survey technique through questionnaires distributed to UPTD employees. Data were analyzed using Moderated Regression Analysis (MRA) to examine both direct effects and the moderating role of job satisfaction. The results indicate that knowledge and work motivation have a positive and significant effect on human resource development. Furthermore, job satisfaction strengthens the relationship between knowledge and work motivation toward human resource development. Specifically, Job Satisfaction (Z) positively influences Human Resource Development (Y) with a path coefficient of 0.98 and a P-Value of 0.000. Work Motivation (X2) positively affects Human Resource Development (Y) with a coefficient of 0.304 and a P-Value of 0.003, and as a moderating variable, it shows a coefficient of 0.254 with a P-Value of 0.005. Knowledge (X1) positively affects Human Resource Development (Y) with a coefficient of 0.31 and a P-Value of 0.001, and as a moderating variable, it shows a coefficient of 0.288 with a P-Value of 0.001. These findings affirm that human resource capacity enhancement depends not only on knowledge and motivation but also on job satisfaction, which plays a crucial role in mediating and strengthening employee performance, particularly within the context of social service institutions that demand dedication and professionalism